Effect of preharvest treatment using jasmonic acid and methyl jasmonate on the physicochemical properties and antioxidant activities of red-fleshed dragon fruit (Hylocereus polyrhizus L.) - Hamzah, Norfarzana; Ramli, Nurul Shazini; Mat Deris, Iffah Haifaa; Moses, Christopher; Azman, Ezzat Mohamad (Universiti Putra Malaysia, 2024)
This study investigated the effect of exogenous plant growth regulators (PGR), namely jasmonic acid (JA) and methyl jasmonate (MeJA), on the physicochemical properties of flesh and peels of red-fleshed dragon fruit (Hylocereus polyrhizus). The fruit was sprayed with 100 and 1,000 ppm of JA and MeJA at 15 and 22 days of anthesis and harvested after 35 days. Then, the flesh and peels were analyzed for total soluble solids (TSS), total betacyanins, betanin, total phenolics (TP), total flavonoids (TF), and color characteristics. The fruit peels contained significantly higher (p<0.05) TP and antioxidant activities compared to flesh. No significant difference was detected between the variables in the peels, except for significantly higher (p<0.05) of total betacyanins (~295.6 and ~299.9 mg/100 g) and TP (~614.1 and 566.1 mg GAE/100 g) were recorded in control and 100 ppm MeJA, respectively. In the flesh, 1,000 ppm MeJA-treated fruit possessed the highest total betacyanins (~139.2 mg/100 g), betanin (~356.0 mg/g), TP (~244.9 mg GAE/100 g), TF (~329.0 mg CE/100 g), Trolox equivalent antioxidant capacity (TEAC) (63.2 μmol TE/g) and reducing power (~21.5 μmol TE/g). Overall, 1,000 ppm MeJA was more effective in enhancing the accumulation of bioactive compounds and antioxidant activities in the flesh of red-fleshed dragon fruit compared to other PGR treatments.